2007
DOI: 10.1136/bmj.39402.463854.ae
|View full text |Cite
|
Sign up to set email alerts
|

New point of care Chlamydia Rapid Test—bridging the gap between diagnosis and treatment: performance evaluation study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 29 publications
5
64
0
Order By: Relevance
“…Others have examined strategies such as selfcollection (non-invasive samples) [1][2][3][4][5][6][7][8] and point-of-care (POC) tests to improve the diagnosis of STIs. [9][10][11][12] Self-collection may be advantageous for women who dislike pelvic examinations or in settings where providers cannot perform pelvic examinations. POC diagnostic STI tests are advocated to increase accurate and timely treatment of infections.…”
Section: Introductionmentioning
confidence: 99%
“…Others have examined strategies such as selfcollection (non-invasive samples) [1][2][3][4][5][6][7][8] and point-of-care (POC) tests to improve the diagnosis of STIs. [9][10][11][12] Self-collection may be advantageous for women who dislike pelvic examinations or in settings where providers cannot perform pelvic examinations. POC diagnostic STI tests are advocated to increase accurate and timely treatment of infections.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that DFA found to be a specific test as it detects the MOMP antigen of C. trachomatis (Mahilum-Tapay et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Such tests should only be used when laboratory facilities are not available 35 since they lack sufficient sensitivity when compared to nucleic acid amplification tests. 36 However, use of POC tests for chlamydia testing outside clinical settings are not recommended because of their poor performance.…”
Section: Poc Testsmentioning
confidence: 99%